Extended Efficacy of Once-Daily Atomoxetine in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The efficacy of atomoxetine administered once daily (final dose 1.3 +/- 0.3 mg/kg; mean 44.5 mg per day; range 10-80 mg per day) in the morning was assessed throughout the day, including evening and early morning, in a total of 197 children, 6 to 12 years of age (71% male), diagnosed with attention-deficit/hyperactivity disorder (ADHD) (69% had combined subtype ADHD, and 35% had comorbid oppositional defiant disorder).